Endometriosis - An Update - Banu, LP; Tasnim, S (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Endometriosis is a common and important health problem of women. The prevalence of endometriosis is difficult to determine. Diagnosis is often difficult and delayed due to close similarity of symptoms of endometriosis with other gynecological disorder. Optimum treatment involves a combination of medical and surgical treatments tailored to the patients needs and response. The objective of the study is to discuss the current updates on diagnosis, treatment and the optimal role of different options in the treatment of endometriosis. The article reviews different medical journals, medline and internet to get the relevant information. The study results showed that both medical and surgical treatments are almost equally effective in pain management there is no evidence that medical treatment improves fertility. Surgical treatment is associated with small but significant improvement in live birth rate. Newer non hormonal drugs are more selective with less metabolic side effects. Surgical treatment is invasive procedure and repeated surgery is associated with major complication. Medical treatment is considered more effective in the long term management of endometriosis. DOI: http://dx.doi.org/10.3329/jbcps.v31i3.20981 J Bangladesh Coll Phys Surg 2013; 31: 144-149